TINGKAT KONSUMSI PROTEIN DI INDONESIA TAHUN 2014-2017 DAN PENGARUHNYA TERHADAP RATA-RATA PENGELUARAN MASAYARAKAT DI DESA DAN DI KOTA - Siska Febrianti (IAIN Batusangkar, 2019)
This study aims to determine the development of the level of protein consumption in Indonesia from 2014-2017 and its effect on the expenditure of residents in the village and in the city. The method used in this study is a qualitative descriptive method with data that has been obtained based on secondary data from the Central Bureau of Statistics (BPS), namely data on average protein consumption according to people's food and average expenditure according to goods groups in Indonesia in 2014 to with 2017. The results of the study indicate that the level of protein consumption in Indonesia that the average protein consumption of this society in 2014 to 2017 is the highest in the consumption of grain commodities compared to other commodities. However, the percentage of grain consumption from 2014 to 2017 has decreased, because there have been many people consuming processed food. This is evidenced by the increase in consumption of finished food in that range of years. Then the expenditure level on vegetable protein commodities in the village is greater than in the city, while the expenditure on commodities of animal protein is greater in the city.